Regional Seminar on Community Support for Education and Participation in Educational Management report. (Thailand : Unesco Principal Regional Office for Asia and the Pacific, 1991)
Within the framework of Unesco's Approved Program and Budget for 1988-1989 under sub-program 0412. Training of Planners, Administrators and Managers, the Unesco Principal Regional Office for Asia and the Pacific, In collaboration with the Indonesian National Commission for Unesco, and the Bureau of Planning, Secretariat General, Ministry of Education and Culture, Indonesia, organized the Regional Seminar on Community Support for Education and Participation in Educational Management, in Ball, Indonesia from 30 October to 4 November 1989.
Chapter One. Introduction -- Chapter Two. Highlights of country presentations -- Chapter Three. Thematic presentations -- Chapter Four. Group reports and site visits to educational institutions -- Chapter Five. Regional co-operation and national follow-up activities.
Includes bibliographical references.
Keywords: EDUCATIONAL MANAGEMENT